2009
DOI: 10.1044/1092-4388(2008/07-0213)
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Children With Cochlear Implants: Perceived Benefits and Problems and the Perception of Single Words and Emotional Sounds

Abstract: The findings regarding age reinforce the importance of early detection and intervention for children's positive quality of life with cochlear implants later in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 44 publications
9
121
2
2
Order By: Relevance
“…Internationally published studies that relate to quality of life after cochlear implantation are gradually increasing in the literature [7][8][9] . Cochlear implantation has been performed for more than 20 years, and we estimate that there are approximately 9000 users in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally published studies that relate to quality of life after cochlear implantation are gradually increasing in the literature [7][8][9] . Cochlear implantation has been performed for more than 20 years, and we estimate that there are approximately 9000 users in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Four articles used ad hoc instruments, which are designed for the purposes of an individual study [Edwards et al, 2012;Schorr et al, 2009;Stacey et al, 2006;WarnerCzyz et al, 2011]. These questionnaires provide considerable information on a child's experience with an implant and use one or a combination of open-ended questionnaires, semistructured interviews, or quantitative instruments.…”
Section: Ad Hoc Instruments In Childrenmentioning
confidence: 99%
“…However, most of the SLH and classroom teachers have noted the exceptional appearance of emotional symptoms of these students when faced with new situations. This fact is possibly related to their communication limits caused by a hearing deficit in the implanted students and a fear of failure to communicate in new contexts of interaction to which they are not accustomed (Remmel & Peters, 2009;Schorr et al 2009). Some studies (Huber & Kipman, 2011;Stinson & Whitmire, 2000;Theunissen, et al, 2012) have shown that early implantation is beneficial both for functional and communication skills (Alegre et al 2014) and helps to prevent and reduce anxiety levels among students with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Children with cochlear implants may experience difficulties in acquiring this type of behavior, particularly if it has been a late implantation, since this leads to a delay in the development of the necessary communication skills (Delgado, 2011;Jiménez, 2011;Rodríguez, 2013). As a consequence, many of the relationship difficulties experienced by implanted children within the school environment are due to their limited production of intelligible speeches as well as a limited understanding of the spoken messages they hear (Martín, Bat-Chava, Lalwani, & Waltzman, 2010;Remmel & Peters, 2009;Schorr, Roth, & Fox, 2009). …”
Section: Introductionmentioning
confidence: 99%